Trichosporon asahii fungaemia in an immunocompetent polytrauma patient who received multiple antibiotics - Ding C.H.; Khaithir T.M.N.; Wahab A.A.; Faiz M.A.; Saarah W.R. (Malaysian Society of Pathologists, 2024)
Trichosporon asahii is a yeast-like fungus that is emerging as an important cause of invasive infections in tertiary medical centres. A 58-year-old Chinese man with no known medical illnesses presented with liver lacerations and multiple fractures following an alleged 12-foot fall at a construction site. The gravity of his injuries and poor haemodynamic status necessitated an intensive care unit (ICU) admission, during which several febrile episodes were detected and multiple antibiotics were administered. After being in the ICU for at least two weeks, a urease-positive yeast was isolated from the patient’s blood. The yeast formed dry, fuzzy and wrinkled white colonies on Sabouraud dextrose agar following prolonged incubation, and produced blastoconidia, true hyphae, pseudohyphae and arthroconidia on slide culture. It was identified biochemically by the ID 32 C kit as T. asahii. The yeast had elevated minimal inhibitory concentration (MIC) values to fluconazole, amphotericin B, flucytosine and all echinocandins tested. In view of this, the patient was treated with voriconazole and was successfully transferred to the general medical ward. © 2020, Malaysian Society of Pathologists. All rights reserved.